The Effectiveness of Using Picture to Improve Students' Reading Skill at seventh-Grade Student of SMP Negeri 8 Seluma - Yuneva Yuneva; Misna Misna; Elva Utami (Edu-Ling: Journal of English Education and Linguistics, 2018)
This study aimed to find out empirical data, to see using picture strategy effective in improving studentsâ€™ reading skill at seventh-grade student of SMP Negeri 8 Seluma. The sample of this study was 62 students taken from the first grade of SMP Negeri 8 Seluma, the students were 31 students of VII-A, as experiment class and 31 students from VII-B, as control class. The method which was used in this study was a quantitative method and the design used in this study was an experiment design. The data collected in this research were analyzed by using t-test. According to the result of statistical calculation, the obtained value of (t-observation) is 2.67 and the value of â€œttâ€ (t table) from the df (60) on the degree of significance of 5% is 2.01. Comparing to the with each value of the degree of significance, the writer finds 2.67 > 2.04. So too is higher than tt or to > tt. The finding of this study it can be concluded that using the picture in teaching reading skill is quite a success by using Picture. It is not only effective to lead students to feel more interesting and enjoy doing activity in the class but also it can give the students the opportunities to be active in teaching a Reading skill.